Overview of Knowledge and Application of Needlestick Risk in Nurse Profession Students - Miftahul Jannah (Universitas Muhammadiyah Tangerang, 2021)
Nurses profession students in carrying out professional practice cannot be separated from the risk of needle sticks. The aim of the study was to describe the knowledge and application of students about the risk of needle sticks. The design of this research is descriptive with the number of respondents 110 students with a simple random sampling technique. This study uses a questionnaire that has previously been tested for validity and reliability. The analysis used is univariate analysis. The results showed that majority of respondents aged 21-25 years were 96 students (87.3%), female respondents were 87 students (79.1%), and program A respondents were 74 students (67.3%). The results of the study explained that 41 students had needle sticks (37.3%) with majority of incidents when closing the needle as many as 18 students (34.6%) and 28 students (68.3%) did not report the incident. The results showed that majority of students' knowledge of needle management, the risk of diseases transmitted from needle sticks, and prevention of needle sticks was lacking as many as 66 students (60.0%). Application of needle management and prevention of needle sticks majority of students was enough for 57 students (51.8%). Majority of students do not know theoretically about the risk of needle sticks. This research expected a basic data for educational institutions in making policies related to socialization and special training for nurse students before carrying out professional practice.Keywords: Knowledge; Needle Punctured; College student